Factors Influencing the Decrease in Visitors to Mampie Beach Tourism, Galeso Village, Wonomulyo District, Polewali Mandar Regency Mandar - Hasanuddin, Hasanuddin; Hisyam, Muhammad; Rasyid M Akib, Abd.; Nurwahid, Hidayat; Nabilawti, Hijrah (Publisher Cv. Inara, 2025)
One of the tourist attractions, especially a very famous beach destination, is Mampie beach which is located in Gleso village, Wonomulyo district, Polewali Mandar district. The Mampie Beach Natural Tourism Area is located in Mampie Hamlet, Galeso Village, Wonomulyo District, Polewali Mandar Regency. This beach, which has a coastline of approximately 3 kilometers, can be reached by two-wheeled or four-wheeled vehicles with a travel time of approximately 30 minutes from Wonomulyo District, which is the trade center of Polewali Mandar Regency. This research was conducted to find out the factors that caused the decline in visitors at the Mampie beach location using qualitative methods by conducting observations, interviews and studying literature and websites on several sites which contain several photos and references from the golden age of this tourist location . The method used in this research is qualitative with observation, interviews and documentation with data analysis techniques: Data Reduction, Data display (Data Presentation) Conclusion Drawing Verification (drawing conclusions). The results of research include several factors that influence the decline in visitors to Mampie beach, namely coastal abrasion and natural disasters, earthquakes. Covid 19, services,Road access to the location, supporting facilities and conflicts of interest between managers and the community.